2020
DOI: 10.1002/ps.6189
|View full text |Cite
|
Sign up to set email alerts
|

Forficula auricularia (Dermaptera) in orchards: Monitoring seasonal activity, the effect of pesticides, and the perception of European fruit growers on its role as a predator or pest

Abstract: BACKGROUND We investigated several aspects that could affect the role of the European earwig (Forficula auricularia) as a generalist predator in orchards: (i) seasonal activity in apple orchards, (ii) effectiveness of two cardboard trap types (roll vs tape) to enhance earwig densities, (iii) the effect of pesticides (chlorpyrifos‐methyl, spinosad, indoxacarb, spirotetramat, pirimicarb, sulphur, fluopyram tebuconazole) on earwig survival and behaviour, and (iv) the perception of European fruit growers of the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Contrary to what was expected, powdered sulphur did not interfere with the activity of A. nemoralis . Limited previous studies similarly found no effects of sulphur‐based compounds on predator activity and behaviour (Niedobova et al., 2021; Satoh et al., 2012). This should support the previous general assumption that inorganic compounds and other fungicides appear to be safer to beneficial arthropods than organic and neurotoxic insecticides (Pekár, 2012; Pérez‐Guerrero et al., 2014).…”
Section: Discussionmentioning
confidence: 84%
“…Contrary to what was expected, powdered sulphur did not interfere with the activity of A. nemoralis . Limited previous studies similarly found no effects of sulphur‐based compounds on predator activity and behaviour (Niedobova et al., 2021; Satoh et al., 2012). This should support the previous general assumption that inorganic compounds and other fungicides appear to be safer to beneficial arthropods than organic and neurotoxic insecticides (Pekár, 2012; Pérez‐Guerrero et al., 2014).…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, direct feeding on fruits can cause fruit disfiguration, rendering the product unmarketable. This has been observed with green peach aphids feeding on fruits before shuck split, as well as European earwigs ( Forficula Auricularia Linnaeus), which can chew into the skin of ripe peaches and generate spots that make fruits unmarketable (Jana et al 2021). Lygus bugs ( Lygus spp., order: Hemiptera) on the other hand are known to create “cat-facing” injury, a characteristic fruit malformation of deep depressions and creases.…”
Section: Introductionmentioning
confidence: 86%
“…The use of crop protection products (which includes pesticides, herbicides and other chemical substances) is one of the most important and recent causes of ecosystem dysfunction and biodiversity loss (Jana et al 2021). Over the past decade, a growing body of evidence has shown that the spraying of these chemical substances on and off crops can affect not only the target plants and animals but also a wide range of non-target organisms, including insects (Desneux et al 2007).…”
Section: Introductionmentioning
confidence: 99%